High Dose Intravenous IgG Therapy Modulates Multiple NK Cell and T Cell Functions in Patients With Immune Dysregulation - McAlpine, Sarah M.; Roberts, Sarah E.; Heath, John J.; Käsermann, Fabian; Issekutz, Andrew C.; Issekutz, Thomas B.; Derfalvi, Beata (Frontiers in Immunology, 2021)
Intravenous immunoglobulin (IVIG) is an effective immunomodulatory treatment for immune dysregulation diseases. However, the mechanisms by which it reduces systemic inflammation are not well understood. NK cell cytotoxicity is decreased by IVIG in women with reduced fertility, but IVIG effects on NK cells in immune dysregulation are less clear. We hypothesized that IVIG modulation of lymphocyte function, especially in NK cells, is important for resolution of inflammation. Our aim was to identify IVIG-induced changes in a cohort of patients with Kawasaki disease (KD) and those that occur broadly in pediatric patients with various immune dysregulatory diseases. Peripheral blood mononuclear cells (PBMCs) of patients with KD or autoimmune/inflammatory diseases were phenotyped pre and post high dose IVIG treatment by flow cytometry. In KD patients, after IVIG infusion Treg cell frequency and the proportion of activated CD25+ immunoregulatory CD56bright NK cells was increased, and multiple lymphocyte subsets showed increased expression of the lymphoid tissue homing receptor CD62L. Importantly, IVIG treatment decreased the frequency of cells expressing the degranulation marker CD107a among cytotoxic CD56dim NK cells, which was reflected in a significant reduction in target cell killing and in a decreased production of multiple pro-inflammatory mediators. Interestingly, the activating receptor CD336 was expressed on a higher proportion of CD56bright NK cells after IVIG in both KD and autoimmune/inflammatory patients while other NK receptors were increased differentially in each cohort. In autoimmune/inflammatory patients IVIG induced the proliferation marker CD71 on a higher percentage of CD56dim NK cells, and in contrast to KD patients, CD107a+ cells were increased in this subset. Furthermore, when PBMCs were stimulated ex vivo with IL-2 or Candida antigen in autologous plasma, more of the CD4+ T cells of KD patients expressed CD25 after IVIG therapy but fewer cytotoxic T cells were degranulated based on CD107a expression. In summary, IVIG treatment in patients with immune dysregulation has multiple effects, especially on NK cell subsets and CD4+ T cells, which are compatible with promoting resolution of inflammation. These novel findings provide insight into the immunomodulatory actions of IVIG in autoimmune and inflammatory conditions.